Influência de tratamentos termo-mecânicos na estrutura e microestrutura da liga Ti-10%pNi obtida por fusão a arco - Cascadan, Daniela [UNESP]; Grandini, Carlos Roberto [UNESP] (My University, 2015)
Titanium alloys are an important class of biomaterials. Apart from the issue of biocompatibility, is very important to consider the mechanical properties of a biomaterial, which are directly related to the microstructure and interstitial elements quantity present. In the present paper, Ti-10wt[%]Ni was produced from the melting of commercially pure titanium and nickel in arc furnace under argon atmosphere. Then a heat treatment was carried out and the sample was hot-rolled. To prove the alloy composition, quantitative chemical analysis was performed. The structure and microstructure of the produced alloy were analyzed by x-ray diffraction, optical and scanning electron microscopy. The results show that the alloy presents predominantly titanium alpha phase (hexagonal compact structure), with proeutectoid lamellar precipitates in eutectoid matrix of alpha phase and intermetallic Ti2Ni.
Influence of thermo-mechanical treatments on the structure and microstructure of Ti-10wt%Ni alloy obtained by arc melting